La conceptualización de la infancia deficiente en los iniciosde la educación especial europea - Herráiz Gascueña, Mariano G. (Revista Española de Pedagogía, 2018)
The establishment of weak mental or mentally retarded and the appearance of the concept of subnormal child, turn up due to the rise of schooling and the access to School of unbiased social classes up to the moment, with the consequent decrease of Scholastic efficiency. The conception / notion and identification of the «Subnormal» will be the result of Schooling and Psychopedagogy because of the constant increase of compulsory schooling in Europe at the beginning of the XXth Century.
Keywords: educación especial; infancia; Revista Española de Pedagogía